PENEGAKAN HUKUM TERHADAP TINDAK KEKERASAN PSIKIS DALAM RUMAH TANGGA - Adriani Adnani (Ensiklopedia of Journal, 2023)
Violence that occurs in the household is not merely a matter of physical violence, although the figures and data in general reveal that the majority of cases of domestic violence that occur are in the type of domestic violence in physical form. Many societies or women are not yet aware that threats and disturbances in the form of psychology in the household are also a form of violence. The results of the study showed that law enforcement in cases of psychological violence in households affecting women as victims was carried out based on Law Number 23 of 2004 concerning the Elimination of Domestic Violence. However, this policy does not function optimally in efforts to deal with psychological violence.Keywords: law enforcement, psychological violence, domestic violence